Effects of pretreatment and drying methods on the quality and stability of dried sweet potato slices during storage. Issue 10 (6th August 2021) - Lagnika, Camel; Riaz, Asad; Jiang, Ning; Song, Jiangfeng; Li, Dajing; Liu, Chunquan; Wei, Qiuyu; Zhang, Min
Abstract: Effects of blanching, osmotic dehydration, and/or ultrasound combined with hot air (HAD), microwave vacuum (MVD), and freeze drying (FD) on the stability of quality attributes of sweet potatoes during 90 days of storage at room temperature were investigated. Pretreated sample prior to two‐step drying (HAD‐MVD) preserved sweet potato color better compared to unblanched and FD samples during storage. X‐ray diffraction clearly showed that the amorphous structure observed with pretreated samples was mainly due to blanching responsible for the disorganization of the starch structure caused by temperature. Physical damage which takes place with blanching treatment in the granule structure and in particular at the level of the crystalline part such as the breaking of intermolecular bonds had a significant impact on a decrease in crystallinity. During 90 days of storage, samples that did not undergo pre‐treatment showed a higher reduction in phenolic content about 75.99% whereas pretreated combined with HAD‐MVD or FD showed a reduction of about 51.31% and 32.27%, respectively. The results demonstrated that MVD caused retention of total carotenoid content, while freeze‐dried samples recorded the highest degradation during storage. Practical applications: Food storage stability addresses one of the foremost problems faced by food processors. Studies on changes in the quality of a food product as a function of time are important to ensure product compliances to food standards. Storage time and processing are the major factors affecting the rate of loss of quality and shelf life of dehydrated sweet potatoes. Recently, osmotic dehydration and/or ultrasound combined with microwave vacuum drying has attracted significant attention in food processing generally because of the recent consumers' trend toward functional foods and stability during storage. The results show that blanching, osmotic dehydration, and/or ultrasound combined with microwave vacuum drying is a potential technique for improving the retention of bioactive compound and stability of sweet potato slices during storage at room temperature.